Multi-taxa surveys: Integrating ecosystem processes and user demands - Magnusson, William Ernest; Lawson, Ben E.; Baccaro, Fabricio Beggiato; Castilho, Carolina Volkmer de; Castley, J. Guy; Costa, Flávia Regina Capellotto; Drucker, Debora P.; Franklin, E.; Lima, Albertina Pimental; Luizâo, Regina Celi Costa; Mendonça, Fernando Pereira; Pezzini, Flávia Fonseca; et al. (Applied Ecology and Human Dimensions in Biological Conservation, 2014)
Globally, natural resource management agencies are increasingly recognizing the importance of long-term ecological research (LTER) for monitoring biodiversity, ranging from relatively simple, known, local-level issues, such as managing tourist impacts in a conservation park, to more complex, multifaceted, pervasive, and far-reaching impacts, such as global climate change. Much previous literature has confused protocols for LTER projects to answer current research questions, with developing a system for long-term ecological monitoring. Contrary to perceptions that these LTER systems are not driven by well-defined objectives, we argue that LTER systems can be designed and implemented with the specific objective of providing a basis for both LTER projects and long-term monitoring. We present an overview of RAPELD, an LTER system developed in Brazil, with comparable infrastructure established in Australia and Nepal. The standardized biodiversity infrastructure and research platform provides a long-term basis for powerful multi-disciplinary, multi-scale analyses. © 2014 Springer-Verlag Berlin Heidelberg. All rights are reserved.